Zum Fortgang der der Agrarreform in Chile - Rother, Klaus (ERDKUNDE, 1974)
As a supplement to a former paper in Erdkunde 1973 a report will be given on a new way towards agrarian reform in Chile. This way is characterized by the creation of family and farmers’ property parcelled out of nationalized farm land as well as the introduction of the principles of market economy. The problems resulting therefrom will be discussed.